Cardiac Abnormalities in Acromegaly Patients: A Cardiac Magnetic Resonance Study. (14th February 2020) - Guo, Xiaopeng; Cao, Jian; Liu, Peijun; Cao, Yihan; Li, Xiao; Gao, Lu; Wang, Zihao; Fang, Ligang; Jin, Zhengyu; Wang, Yining; Xing, Bing
Abstract : Cardiac abnormalities are the most common and deadly comorbidities of acromegaly. Assessments using cardiac magnetic resonance (CMR) imaging in acromegaly patients are rare. We aimed to evaluate the frequencies of left ventricular hypertrophy (LVH), interventricular septum hypertrophy (IVSH), LV systolic dysfunction (LVSD), right ventricular systolic dysfunction (RVSD), and myocardial fibrosis (MCF) and detailed quantitative parameters in acromegaly patients using CMR and analyze their correlations with clinical features. Sixty-one patients were enrolled in this study. The rates of LVH, IVSH, LVSD, RVSD, and MCF were 26.2%, 27.9%, 8.2%, 9.8%, and 14.8%, respectively. The average LV mass, LV mass index, IVS thickness, LV and RV free wall thickness, and LV and RV ejection fractions were 114.4 g, 60.0 g/m 2, 9.6 mm, 7.2 mm, 2.9 mm, 59.9%, and 56.6%, respectively. The LV mass index was larger (68.9 ± 26.0 vs. 48.8 ± 10.6 g/m 2 ), the IVS was thicker (10.3 ± 2.8 vs. 8.8 ± 1.8 mm), and the LV (57.6 ± 12.3% vs. 62.8 ± 4.8%) and RV ejection fractions (54.6 ± 8.7% vs. 59.2 ± 5.9%) were lower in male patients than in female patients (all p < 0.05 ). Age, body mass index (BMI), disease duration, and hypertension were associated with cardiac abnormalities (all p < 0.05 ). In conclusion, structural and functional cardiac abnormalities can be comprehensively evaluated by CMR in acromegaly patients. Gender greatly affects the presence of cardiac abnormalities. Age, BMI, disease duration, and hypertension but not GH or IGF-1 levels are associated clinical factors.